EFFECT OF BRAND IMAGE DAN PRODUCT QUALITY ON PURCHASE DECISION OF SCARLETT WHITENING IN MEDAN CITY - Sinaga, Mega Astria; Adlina, Hafiza (Simangunsong : Journal of Business Administration, Management, Economic And Accounting, 2023)
Scarlett Whitening is a new brand but very quickly famous and sold among the community amid intense competition in the Indonesian cosmetic industry that gave rise to many new cosmetic brands in recent years. This study aims to determine how the influence of brand image and product quality on the decision of Scarlett Whitening products in Medan both partially and simultaneously. The type of research used in this study is quantitative research with associative approach. Sampling technique is purposive sampling of 100 respondents. Data analysis techniques used are validity test, reliability test, classical assumption test, multiple linear regression test, T test, F test and coefficient of determination test. The results showed that the brand image and product quality have a positive and significant effect on purchasing decisions Scarlett Whitening products partially and simultaneously. Correlation coefficient value of 0.870 which indicates a fairly strong correlation between brand image and product quality variables on purchasing decisions. R Square value of purchase decision variable of 75.7% can be explained by brand image and product quality variables, while the remaining 24.3% is influenced by other variables that are not contained in the study.